Model Collaborative Governance Dalam Pengelolaan Dan Pengembangan Ekosistem Pelabuhan Patimban Di Kabupaten Subang - Diah Andani (The World of Public Administration Journal, 2025)
Abstract The Patimban Port in Subang Regency is a national strategic project that plays a crucial role in supporting logistics development and industrialization within the Rebana Region. However, the complexity of actors and overlapping cross-sectoral authorities requires a collaborative governance approach in managing the port ecosystem. This study aims to analyze the dynamics of collaborative governance in the management and development of the Patimban Port ecosystem and to formulate a collaboration model that aligns with the characteristics of multi-level governance in the region. The research employs a qualitative approach with a case study design through in-depth interviews, field observations, and document analysis of national and regional policies. Thematic analysis was conducted with reference to the collaborative governance model proposed by Ansell and Gash. The findings indicate that inter-agency collaboration has not functioned effectively due to unequal starting conditions between the central and local governments, fragmented institutional design, limited facilitative leadership capacity at the local level, and dialogic processes that are more informative than deliberative. Power asymmetries, the absence of formal collaborative platforms, and low participation from coastal communities further exacerbate the gap between national policy directions and local needs. Based on these findings, this study develops the Patimban Collaborative Governance Model, emphasizing three main pillars: establishing cross-actor collaboration platforms, strengthening facilitative leadership of local governments, and creating structured participatory mechanisms for affected communities. This study contributes to the development of collaborative governance concepts in the context of strategic infrastructure and provides practical recommendations for national, provincial, and Subang Regency governments in building a more inclusive, adaptive, and sustainable port governance system. Keywords:  Collaborative Governance   Abstrak Pelabuhan Patimban di Kabupaten Subang merupakan proyek strategis nasional yang berperan penting dalam pengembangan logistik dan industrialisasi Kawasan Rebana. Namun, kompleksitas aktor dan tumpang tindih kewenangan lintas sektor membuat pengelolaan ekosistem pelabuhan memerlukan pendekatan tata kelola yang kolaboratif. Penelitian ini bertujuan menganalisis dinamika collaborative governance dalam pengelolaan dan pengembangan ekosistem Pelabuhan Patimban serta merumuskan model kolaborasi yang sesuai dengan karakter tata kelola multi-level di wilayah tersebut. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara mendalam, observasi lapangan, dan studi dokumentasi terhadap kebijakan pusat dan daerah. Analisis dilakukan secara tematik dengan merujuk pada model collaborative governance Ansell dan Gash. Hasil penelitian menunjukkan bahwa kolaborasi antarlembaga belum berjalan efektif karena adanya ketidakseimbangan starting conditions antara pemerintah pusat dan daerah, desain kelembagaan yang terfragmentasi, terbatasnya kapasitas kepemimpinan fasilitatif di tingkat daerah, serta proses dialog yang lebih bersifat informatif daripada deliberatif. Ketimpangan kewenangan, minimnya platform kolaborasi formal, dan rendahnya partisipasi masyarakat pesisir memperkuat gap antara arah kebijakan pusat dan kebutuhan lokal. Berdasarkan temuan tersebut, penelitian ini mengembangkan Model Collaborative Governance Patimban yang menekankan tiga pilar utama: pembentukan platform kolaborasi lintas aktor, penguatan kepemimpinan fasilitatif pemerintah daerah, dan mekanisme partisipatif terstruktur untuk masyarakat terdampak. Penelitian ini berkontribusi pada pengembangan konsep collaborative governance dalam konteks infrastruktur strategis serta memberikan rekomendasi praktis bagi pemerintah pusat, provinsi, dan Kabupaten Subang dalam membangun tata kelola pelabuhan yang lebih inklusif, adaptif, dan berkelanjutan. Katakunci: Collaborative Governance